TANTANGAN KEBERLANJUTAN PEKEBUN KELAPA SAWIT RAKYAT DI KABUPATEN PELALAWAN, RIAU DALAM PERUBAHAN PERDAGANGAN GLOBAL - Hutabarat, Sakti (Masyarakat Indonesia, 2018)
Oil palm smallholders are potential actors to be included in the global palm oil market. Smallholder plantations account for 41.4% of total oil palm plantation areas and represents 36.6% of total CPO produced in Indonesia in 2015. The number of farmers involves in oil palm plantation encompass 2.3 million farmers which have been an important driver for economic growth in rural areas. However, oil palm smallholders are vulnerable from issues related to unsustainable production including environmental, social and legal issues which might lower access and exclude smallholder access to global market. The objective of this study is to analyze position and capacity of oil palm smallholders in facing global change in international market. Population of this study is oil palm smallholder farmers in Ukui Subdistrict, Pelalawan District, Riau Province which consist of RSPO-certified independent smallholders, Non-certified independent smallholders, and RSPO-certified scheme smallholders. The sample size were 220 farmers and chosen randomly from each group (80, 60 and 80 farmers for each group respectively). The study found that majority of the farmers still apply traditional practices in their plantations and far below the standard of good agricultural practices and certification standards. The challenges faced by the Amanah Association to obtain RSPO certificate is not easy to follow by other smallholders. Therefore, external supports from government and private actors are needed to improve farmers’ capacity to meet and comply with certification and to include small-scale farmers in the palm oil global supply chain.